MICROAGGRESSIONS OF HIGH SCHOOL STUDENTS IN TERMS OF SUBCULTURES IN SAMARINDA CITY - Andi Wahyu Irawan (Universitas Pendidikan Indonesia, 2022)
Research related to microaggressions has been centered on the western context and limited to the Indonesian context. Whereas a pluralistic country like Indonesia needs studies and information related to this problem to encourage harmonious schools. This study aims to describe the microaggression level of high school students in terms of subcultures in the Bugis Tribe, Kutai Tribe, Javanese Tribe, Dayak Tribe, and Banjar Tribe in Samarinda City. The research method uses quantitative research with the type of survey research. A total of 500 students from 5 schools filled out the survey. The instrument used in this study was the Racial and Ethnic Microaggression Scale (REMS), adapted from Nadal (2011). Data analysis using descriptive analysis and one-way ANOVA test. The results showed that respondents preferred more indecisive and unsuitable for the scale of microaggression experience measurement. The experience of microaggression is also experienced differently by subcultures. This research became the basis that microaggression occurs in schools, albeit with low intensity. However, guidance and counseling teachers need to be competent in reducing microaggressions in schools.